Spatiotemporal Relationship of Brain Pathways during Human Fetal Development Using High-Angular Resolution Diffusion MR Imaging and Histology - Vasung, Lana; Raguz, Marina; Kostovic, Ivica; Takahashi, Emi (Frontiers in Neuroscience, 2017)
In this study, we aimed to identify major fiber pathways and their spatiotemporal relationships within transient fetal zones in the human fetal brain by comparing postmortem high-angular resolution diffusion MR imaging (HARDI) in combination with deterministic streamline tractography and histology. Diffusion weighted imaging was performed on postmortem human fetal brains [N = 9, age = 18–34 post-conceptual weeks (PCW)] that were grossly normal with no pathologic abnormalities. After HARDI was performed, the fibers were reconstructed using Q-ball algorithm and deterministic streamline tractography. The position of major fiber pathways within transient fetal zones was identified both on diffusion weighted images and on histological sections. Our major findings include: (1) the development of massive projection fibers by 18 PCW, as compared to most association fibers (with the exception of limbic fibers) which have only begun to emerge, (2) the characteristic laminar distribution and sagittal plane geometry of reconstructed fibers throughout development, (3) the protracted prenatal development shown of the corpus collosum and its' associated fibers, as well as the association fibers, and (4) the predomination of radial coherence in the telencephalon (i.e., majority of streamlines in the telencephalic wall were radially oriented) during early prenatal period (24 PCW). In conclusion, correlation between histology and HARDI (in combination with Q-ball reconstruction and deterministic streamline tractography) allowed us to detect sequential development of fiber systems (projection, callosal, and association), their spatial relations with transient fetal zones, and their geometric properties.